EFEKTIVITAS PENERAPAN SMART LIVING MELALUI APLIKASI TEMAN BUS DI KOTA PALEMBANG - Bagas Putra Purnama; M. Qur’anul Kariem; Isabella Isabella (Governance, 2024)
This research aims to determine the effectiveness of implementing Smart Living through the Teman Bus application in Palembang City and providing benefits both theoretically and practically. Application Teman Bus is one of the public transport development programs in urban areas. This application is road-based using technology and non- cash based to improve the safety and security of people's mobility. Application Teman Bus the one in Palembang City is a concept design Buy the Service (BTS) was first issued by the Ministry of Transportation of the Republic of Indonesia. The Teman Bus application will automatically add regulations and be neater, and more sophisticated for transportation users in the city of Palembang. Potency Smart Living in Palembang City supports the realization Smart City. The research method used is a qualitative method that aims to collect accurate and objective data related to the issue being discussed, data collection techniques that involve interaction, including observation, interviews, and documentation. Smart Living is part of the six concept areas Smart City discusses criteria and concepts on how to better manage the quality of life and habits (culture) in an area).